Features of the early tintinnabuli style in the works by Arvo Pärt: interaction а word and a number - Gomeniuk, Svitlana; Tarasenko, Nazarii (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2023)
Relevance and scientific novelty of the selected topic of the research. The work of Arvo Pärt is regularly covered in Ukrainian musicology, however, the issue of the interaction of his compositional technique with the verbal text used to be a part of a broader scientific problem—such as the author’s style, modern choral writing, etc. At the same time, a comparison of the methods of applying the tintinnabuli technique in works with and without text was not undertaken yet. Indeed, the comparative method allows a better understanding of how word and number—two main compositional factors in the works of A. Pärt—work. The opportunity to clarify our ideas about the creative method of one of the most performed contemporary composers, as well as the use of rare works by A. Pärt as research material, ensures the relevance of the article. In addition, the performer’s view of the choral work of A. Pärt, reflected in the article, has a certain novelty. The aim of the article is to identify the specifics of the composer’s work with the verbal text, to establish the ways of interaction between the number and the word in the choral works of A. Pärt, to substantiate the choice of performing means that are adequate in terms of style. Main results and conclusions: 1) both instrumental and choral works by A. Pärt are algorithmic compositions based on numerical series as the fundament of the melodic voice; 2) in both groups of works, the numerical series are not formed on immanent musical patterns, but are borrowed from outside; 3) the numerical series of the instrumental compositions “Für Alina” and “Cantus in Memory of Benjamin Britten” are increasing and/or decreasing arithmetic progressions: each subsequent modus-block of the melodic voice contains a tone more/less than the previous one; 4) the numerical sequences of works with verbal text are based on the syllabic structure of the word: in the works "Missa Syllabica", "Cantate Domino" the number of sounds in each modus-block corresponds to the number of syllables in the word. A hypothetical judgment is made that the work “Summa” is a creative experiment of Arvo Pärt: the composer uses the method of forming numerical series not on the basis of the word (as in other choral compositions), but on the basis of number (as in instrumental compositions). Later, the composer revised this approach to working with the word, he’s created an instrumental version of this work for string quartet. The way the tintinnabuli technique presents in A. Pärt’s choral works emphasizes the priority of the verbal text.